L’urbanistica di Ferrara durante il pontificato di Paolo V (1605-1621) - Giulio Carpanelli (Annali Online dell'Università di Ferrara. Sezione Lettere, 2023)
Since 1598, during the period of the papal domination in Ferrara, the so-called Legation Age, except the building of the huge defensive structure no urban city works were realized. The reason was due to various factors: economic crisis, a new government (the capital of the duchy had become a district outpost), absence of factories. As above mentioned, the Fortress was the only relevant work but, to have it completed, a whole quarter, together with some Este ‘delizie’, had been completely destroyed. The Fortress was built during the dominion of Pope Paolo V, and as an important construction, it involved some of the best military engineers of that period. What’s more, it was placed inside the city, unlike other fortresses of the same period. Modifications of the city walls were realized, an example is the construction of Porta Paola, together with some little but relevant changes. The fact that during the papal domination the military city planning considered defence structures mainly against Venice and the city itself, because of possible invasions or city uprising, should be noted. If it’s true that the Legation Age has been positively considered in recent years by the historians, the city planning of that time remains unsatisfactory.